2021
DOI: 10.3390/nu13113978
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Habitual Mineral Intake with New-Onset Prediabetes/Diabetes after Acute Pancreatitis

Abstract: Associations between habitual dietary intake of minerals and glucose metabolism have been extensively studied in relation to metabolic disorders. However, similar research has yet to be conducted in individuals after acute pancreatitis (AP). The main aim was to investigate the associations between habitual intake of 13 minerals and glycaemic status: new-onset prediabetes/diabetes after AP (NODAP), pre-existing prediabetes/type 2 diabetes (T2DM), and normoglycaemia after AP (NAP). Associations between the dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 110 publications
0
4
0
Order By: Relevance
“…Interestingly, the study found that the insulin-resistant group had significantly higher total cholesterol/HDL cholesterol and triglyceride and lower HDL cholesterol compared to the non-insulin-resistant group [ 21 ]. Another study by Norbitt et al used the data from the ANDROMEDA project to assess dietary intake [ 22 ]. Subjects included in the study were diagnosed with AP between 2015–2019 with the most updated international diagnosis guideline and either did or did not use anti-diabetic medication or insulin use.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the study found that the insulin-resistant group had significantly higher total cholesterol/HDL cholesterol and triglyceride and lower HDL cholesterol compared to the non-insulin-resistant group [ 21 ]. Another study by Norbitt et al used the data from the ANDROMEDA project to assess dietary intake [ 22 ]. Subjects included in the study were diagnosed with AP between 2015–2019 with the most updated international diagnosis guideline and either did or did not use anti-diabetic medication or insulin use.…”
Section: Resultsmentioning
confidence: 99%
“…The study excluded individuals with diabetes type 1 or gestational diabetes, chronic pancreatitis, intraoperative diagnosis of pancreatitis or post-endoscopic retrograde cholangiopancreatography pancreatitis. The results revealed a significant difference in the mean intake of copper between the 3 groups, as well as a significant negative association between the fasting plasma glucose and copper intake in the NAP group [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most nutrients do not exist on their own and are often combined with other nutrients or compounds in the human diet. Specifically, dietary fibre rarely appears on its own in natural food and is often present in the form of a plant cell wall with other nutrients (such as starch, vitamins, and minerals) [21,22]. The primary plant cell wall is the most common form of dietary fibre in the human diet, with a structured network of cellulose and hemicellulose embedded in a network of pectin, while the secondary plant cell wall is the less common form, which is made up of lignin and cellulose [23].…”
Section: Effects On Nutrients' Availabilitymentioning
confidence: 99%
“…Nonetheless, there are no specific guidelines for optimal nutrition therapy for new-onset diabetes after AP, with patients typically receiving generalised type 2 diabetes nutrition advice focusing on macronutrient distribution, portion sizes, and intake of minimally processed foods [ 27 , 28 ]. Emerging evidence suggests a role of micronutrients, particularly mineral intake, in the development of new-onset diabetes after AP [ 29 , 30 ]. To date, intake of other micronutrients (specifically vitamin intake) has never been investigated in the context of new-onset diabetes after AP.…”
Section: Introductionmentioning
confidence: 99%